DOI: 10.14264/uql.2015.1057
|View full text |Cite
|
Sign up to set email alerts
|

A novel, low-energy process route for primary production of copper utilising synergistic hydro- and pyro-metallurgical processes

Abstract: In this thesis, a novel, low-energy process route for primary production of copper that utilises synergies between hydro-and pyro-metallurgical processes is proposed. The process involves precipitating copper from an acidic leach solution by pH adjustment. This precipitation step separates and concentrates the copper from the leach solution. The concentrated copper precipitate is then fed to a pyrometallurgical copper smelter or converter. Research on this process focused on four areas:• The copper phases prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 64 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…Experimental measurements have shown that moisture is progressively reduced on heating. Heating to 300°C will remove all water of crystallisation associated with the gypsum, while heating further to 450°C will decompose all of the hydroxides associated with the basic copper sulphate, expelling steam and leaving copper oxides and sulphates (Hawker 2015). The process flow diagram showing this variant is shown in Figure 4.…”
Section: The Synergistic Copper Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental measurements have shown that moisture is progressively reduced on heating. Heating to 300°C will remove all water of crystallisation associated with the gypsum, while heating further to 450°C will decompose all of the hydroxides associated with the basic copper sulphate, expelling steam and leaving copper oxides and sulphates (Hawker 2015). The process flow diagram showing this variant is shown in Figure 4.…”
Section: The Synergistic Copper Processmentioning
confidence: 99%
“…The liquidus temperature of the fayalite slags in copper converter slags is shown in Figure 9. Thermochemical calculations have also been undertaken to examine the potential use of PCP as a direct feed into copper converter technologies, and the effects of technology, matte grade, slag composition, and oxygen enrichment on the output from these processes (Hawker et al 2014;Hawker 2015). These preliminary calculations clearly demonstrate that, in the case of copper converting, if copper reverts and other inert materials currently used to control reactor temperature were partially replaced by PCP copper, the productivity through the converter section of the plant could be increased by between 5 and 35% depending on the technology and operating practice.…”
Section: Smelting and Convertingmentioning
confidence: 99%
See 3 more Smart Citations